Judge's Considerations in Land Sale and Purchase Agreements Through Absolute Power of Attorney (Case Study of Denpasar District Court Decision Number 679/Pdt.G/2021/PN Dps - Achmad Murtadho; Elsa Assaris (LEGAL BRIEF, 2024)
Civil Lawsuit Decision Number 679/Pdt.G/2021/PN.Dps which states that the Deed of Strengthening Sale and Purchase which is an Absolute Power of Attorney Deed made before a Notary is SAH and binding. This is contrary to the law of binding sale and purchase agreements which are often used by community, but the absolute power of attorney agreement in binding sale and purchase is also not specifically regulated in statutory regulations: how the judge considers the agreement to bind the sale and purchase of land through absolute power (Case Study of Denpasar District Court Decision Number 679/Pdt.G/2021/ PN Dps); This research uses a type of normative juridical research, namely research that focuses on examining the rules or norms in positive law; Civil Decision in Lawsuit Number 679/Pdt.G/2021/PN.Dps Provides legal considerations that because the payment of the land purchase price has been made in full by the buyer, the power of attorney used in PPJB Deed Number 32 and Power of Attorney to Sell Deed Number 33 cannot be categorized as a form of absolute power whose use is prohibited. Regarding PPJB which is paid in full, based on research results, this is one of the conditions that is absolutely mandatory to be fulfilled if the parties are to exercise absolute power in the Land PPJB. (Making PPJB Land which uses absolute power of attorney has also fulfilled its obligation to provide legal protection and certainty for the parties. The agreement between the parties to make an absolute power of attorney is made based on the principle of freedom of contract as regulated in Article 1338 of the Civil Code. The parties are free to arrange the agreement as they wish as long as This does not conflict with law and legislation, morals, decency, decency and religion, public interests (van openbare order. The granting of power of attorney which cannot be revoked is valid if the agreement which is the basis for the granting of power has valid legal reasons.